Oliver Heaviside maverick mastermind of electricity - Mahon, Basil (London, United Kingdom The Institution of Engineering and Technology, 2009)
Oliver Heaviside (1850-1925) was one of the great pioneers of electrical science. His ideas led to huge advances in communications and now form much of the bedrock of electrical engineering every textbook and every college course bears his stamp. Despite having little formal education he created the mathematical tools that were to prove essential to the proper understanding and use of electricity. At first his ideas were thought to be outrageous and he had to battle long and hard against ignorance, prejudice and vested interests to get them accepted. Yet they are now so much a part of everyday electrical science that they are simply taken for granted and our great debt to him is rarely acknowledged. Caring nothing for social or mathematical conventions, he lived a fiercely independent life, much of the time close to poverty. His writings reveal a personality like no other and are laced with wickedly irreverent humour; he is by far the funniest author of scientific papers. Basil Mahon combines an account of Heaviside's life with an insight into his scientific thinking and the reasons for its enduring influence.
Electronic reproduction.
Keywords: Heaviside, Oliver -- 1850-1925.; Electrical engineers -- Great Britain -- Biography; Electrical engineering -- History -- 19th century. -- Great Britain; Electrical engineering -- History -- 20th century. -- Great Britain; Electronic books